An epigenetic clock to estimate the age of living beluga whales. (3rd February 2021) - Bors, Eleanor K.; Baker, C. Scott; Wade, Paul R.; O'Neill, Kaimyn B.; Shelden, Kim E. W.; Thompson, Michael J.; Fei, Zhe; Jarman, Simon; Horvath, Steve
Abstract: DNA methylation data facilitate the development of accurate molecular estimators of chronological age or "epigenetic clocks." We present a robust epigenetic clock for the beluga whale, Delphinapterus leucas, developed for an endangered population in Cook Inlet, Alaska, USA. We used a custom methylation array to measure methylation levels at 37, 491 cytosine–guanine sites (CpGs) from skin samples of dead whales ( n = 67) whose chronological ages were estimated based on tooth growth layer groups. Using these calibration data, a penalized regression model selected 23 CpGs, providing an R 2 = 0.92 for the training data; and an R 2 = 0.74 and median absolute age error = 2.9 years for the leave one out cross‐validation. We applied the epigenetic clock to an independent dataset of 38 skin samples collected with a biopsy dart from living whales between 2016 and 2018. Age estimates ranged from 11 to 27 years. We also report sex correlations in CpG data and describe an approach of identifying the sex of an animal using DNA methylation. The epigenetic estimators of age and sex presented here have broad applications for conservation and management of Cook Inlet beluga whales and potentially other cetaceans.